Torneamento do aço endurecido AISI D6 utilizando mínima quantidade de fluido de corte - Bonfá, Miguel Mandú (2013)
Hardened steel is usually machined under dry condition. Application of an overhead flood cooling generally leads to premature tool failure because the heat generated that helps the shearing process needed to form the chips is reduced by its cooling action. This work proposes to study the application of MQF (Minimum Quantity of Cutting Fluid) when turning the heat treated hardened AISI D6 steel with PCBN (Polycrystalline Cubic Boron Nitride) tools and compare with the dry machining. The spray of a vegetable based cutting fluid was applied between the workpiece and the flank face of the tool. Overhead direction of the MQF and between the secondary flank face of the tool and the workpiece were also tested. Tool wear (VB), surface roughness (Ra, Rz e Rq) and cutting forces (Fx, Fy e Fz) were considered the output variables and the results were compared to those obtained when cutting in dry condition. The influence of the input parameters: cutting speed and feed rate, as well as their interactions were statistically analyzed. Considering the tool wear and the surface roughness, the application of the cutting fluid by the MQF technique in the direction between the flank face and the workpiece showed better results than the dry condition when employing the lowest feed rate of 0.05 mm/rev, regardless the cutting speed used. This cutting fluid application technique also presented good results when the cutting speed of 310 m/min was tested, regardless the feed rate employed. Therefore, this cutting speed should be recommended for high production in turning of AISI D6 steel with the MQF technique. The application of MQF through other directions (overhead and between the secondary flank face and the workpiece) also showed competitive results.